3D surface reconstruction for laparoscopic computer-assisted interventions: Comparison of state-of-the-art methods - Groch, A.; Seitel, A.; Hempel, Sarah-Marie; Speidel, S.; Engelbrecht, Rainer; Penne, Jochen; Höller, Kurt Emmerich; Röhl, S.; Yung, K.; Bodenstedt, S.; Pflaum, Felix; Dos Santos, T. R.; et al. (Medical Imaging 2011: Visualization, Image-Guided Procedures, and Modeling, 2011)
One of the main challenges related to computer-assisted laparoscopic surgery is the accurate registration of pre-operative planning images with patient's anatomy. One popular approach for achieving this involves intraoperative 3D reconstruction of the target organ's surface with methods based on multiple view geometry. The latter, however, require robust and fast algorithms for establishing correspondences between multiple images of the same scene. Recently, the first endoscope based on Time-of-Flight (ToF) camera technique was introduced. It generates dense range images with high update rates by continuously measuring the run-time of intensity modulated light. While this approach yielded promising results in initial experiments, the endoscopic ToF camera has not yet been evaluated in the context of related work. The aim of this paper was therefore to compare its performance with different state-of-the-art surface reconstruction methods on identical objects. For this purpose, surface data from a set of porcine organs as well as organ phantoms was acquired with four different cameras: a novel Time-of-Flight (ToF) endoscope, a standard ToF camera, a stereoscope, and a High Definition Television (HDTV) endoscope. The resulting reconstructed partial organ surfaces were then compared to corresponding ground truth shapes extracted from computed tomography (CT) data using a set of local and global distance metrics. The evaluation suggests that the ToF technique has high potential as means for intraoperative endoscopic surface registration. © 2011 SPIE.

Gastrointestinal surgery 2025 - Changes emerging with information science - Hornegger, Joachim; Höller, Kurt Emmerich; Hempel, Sarah-Marie (Endoskopie heute, 2011)
Gastrointestinal surgery is influenced by developments in information science. In particular, it is expected that information science will serve as a basis for NOTES procedures. In this contribution we provide an overview over the expected progress and associated problems. High innovation speed in technology and the continuously increasing complexity of technical systems open up great opportunities, but imply also problems that have to be assessed actively by physicians and surgeons. © Georg Thieme Verlag KG Stuttgart New York.

In-vitro Evaluation von endoskopischer Oberflächenrekonstruktion mittels Time-of-Flight-Kameratechnik - Groch, Anja; Hempel, Sarah-Marie; Speidel, Stefanie; Höller, Kurt Emmerich; Engelbrecht, Rainer; Penne, Jochen; Seitel, Alexander; Röhl, Sebastian; Yung, Kwong; Bodenstedt, Sebastian; Pflaum, Felix; Kilgus, Thomas; et al. (Workshop Bildverarbeitung für die Medizin, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEH.invitr

Rectification of Endoscopic Images by Gravity - Höller, Kurt Emmerich; Hempel, Sarah-Marie; Schneider, Armin; Jahn, Jasper; Gutierrez, Javier; Wittenberg, Thomas; Hornegger, Joachim; Feußner, Hubertus (Proc. Pattern Recognition in Medical and Health Engineering ’10, 2010)